Mindful Decision Makers: The Influence of Mindfulness on Decision Making Style, Competence, and Outcomes - REB, Jochen (Institutional Knowledge at Singapore Management University, 2011)
In the present research, we examine the influence of mindfulness on decision making style, competence, and outcomes. Mindfulness can be defined as open, non-judgmental present-moment oriented awareness (Brown & Ryan, 2003; Kabat-Zinn, 1992). Mindfulness has been shown to be positively related to a variety of psychological wellbeing related variables, including lower depression and higher emotion regulation (Brown & Ryan, 2003). We predict that mindfulness will be positively associated with desirable aspects of decision making style, with decision making competence, and will be negatively associated with detrimental decision outcomes. In Study 1, we found that mindfulness was positively related to two aspects of decision making style: decision making self-esteem (r = .27, p < .05) and vigilance (r = .34, p < .01). Mindfulness was negatively related to hyper-vigilance, an undesirable decision making approach (r = -.29, p < .05). Mindfulness was unrelated to buckpassing and procrastination. Further, mindfulness was positively related to self-control (r = .39, p < .01). In Study 2, mindfulness predicted the Consistency in Risk Perception component of the Adult Decision-Making Competence test (r = .19, p < .05). Further, mindfulness was negatively related to a summary index of detrimental decision outcomes (r = -.33, p < .01) as well as specific outcomes such as buying new apparel but not wearing them, having a check bounce, and forgetting a birthday.